SNAP benefits and childhood asthma. (January 2019) - Heflin, Colleen; Arteaga, Irma; Hodges, Leslie; Ndashiyme, Jean Felix; Rabbitt, Matthew P.
Abstract: Anecdotal and descriptive evidence has led to the claim that some low-income households may face a "eat or breathe" tradeoff, but quantitative evidence is scarce. We link Medicaid claims data to monthly Supplemental Nutritional Assistance Program (SNAP) participation data from the state of Missouri from 2010 to 2013 to explore monthly patterns in children's emergency room (ER) claims for asthma and to examine whether these patterns are sensitive to the timing and amount of SNAP benefits. This allows us to empirically test whether SNAP households with Medicaid insurance face trade-offs between food and medicine that increases the likelihood that a child in a SNAP and Medicaid household will go to the ER for asthma at the end of the month. While we do not find overwhelming evidence that the timing of SNAP benefits receipt are associated with the timing of asthma-related ER visits, we do find clear evidence that increased SNAP benefits are associated with a reduction in the overall probability of an asthma-related ER visit. Highlights: Previous evidence suggests that households may face a "eat or breathe" tradeoff. The timing of SNAP benefits is not associated with ER visits for childhood asthma. Higher SNAP benefits are associated with a reduction in ER visits for childhood asthma.